Differences in baseline risk estimated by physicians and patients with early breast cancer. (1st October 2021) - Mori, Makiko; Yoshimura, Akiyo; Sawaki, Masataka; Hattori, Masaya; Kotani, Haruru; Adachi, Yayoi; Iwase, Madoka; Kataoka, Ayumi; Sugino, Kayoko; Horisawa, Nanae; Ozaki, Yuri; Iwata, Hiroji; et al.
Abstract: Background: Physicians recommend adjuvant therapy to patients based on baseline risk. A common recognition for baseline risk between patients and physicians is critical for successful adjuvant therapy. We prospectively investigated the differences in estimated baseline risk between physicians and patients with early breast cancer. Methods: This analysis was performed at a single institution in Japan. Early breast cancer patients over 18 years old were enrolled after surgery. After explaining the pathological results, physicians asked each patient about an estimated baseline risk. Differences in estimated baseline risk were defined as the baseline risk estimated by patients minus the baseline risk estimated by physicians. The primary endpoint was that the number of patients who estimate baseline risk higher than physicians was higher than those who estimate a lower baseline risk. The secondary endpoints were differences in estimated baseline risk by stage, subtype and the influence of patient factors to differences in estimated baseline risk. Results: From July 2017 to December 2018, 262 patients were enrolled. Among the 262 patients, 190 estimated a higher baseline risk than physicians, 53 estimated a lower baseline risk and 19 estimated the same. Overall, patients estimated a significantly higher baseline risk than physicians ( P < 0.001). Differences in estimated baseline risk was significantly smaller in patients who knew the term 'baseline risk' than patients who did not ( P = 0.0037). Differences in estimated baseline risk were also significantly smaller in patients with stage II breast cancer than patients with stage I ( P = 0.0239). However, there were no statistically significant differences of differences in estimated baseline risk according to other factors. Conclusions: Patients with early breast cancer estimated a significantly higher baseline risk than physicians. Physicians should accurately explain baseline risk to patients for shared decision making. Abstract : Patients with early breast cancer estimated a significantly higher baseline risk than physicians. Physicians should accurately explain baseline risk to patients for shared decision making.